Experimental and numerical characterisation of rheological properties of a drop test response of a ballistic plastilina. (May 2020) - Gilson, L.; Rabet, L.; Imad, A.; Coghe, F.
Highlights: Plastilina used as a ballistic witness material (BWM) behind the armour to evaluate the backface signature (BFS). Experimental and modelling approaches to determine the response of the specific ballistic plastilina. High-speed camera used for measuring the penetration depth of a steel ball into the plastilina from drop test. Numerical simulation of the drop test performed by taking into account the mechanical properties of the plastilina. Abstract: Plastilina is often used as a ballistic witness material (BWM) behind the armour to evaluate the backface signature (BFS). Indeed, it is cheap, reusable and it keeps its deformation after being impacted. Moreover, while it aims at evaluating the performance of ballistic protections when no perforation occurs, it can be subjected to a very wide range of strain/shear rates during a ballistic impact. Therefore, there is a need to improve the knowledge about the mechanical/rheological response of such a material. This paper proposes both experimental and modelling approaches to determine the response of the specific ballistic plastilina red Weible® over a wide range of shear/strain rate. A capillary rheometry analysis with control of temperature was performed up to 8.10 4 s −1 . The corrections of Rabinowitsch and Bagley were applied and an attempt of the analysis of Mooney was considered. From the rheology of plasticine, a two-parameters based power-law constitutive equation was deduced. An experimental drop test was carried out using a specific standard setup. A high-speed camera was used for measuring the penetration depth of a steel ball into the plastilina. A numerical simulation of the drop test was performed by taking into account the mechanical properties of the plastilina. A good correlation was observed between the experimental and numerical results in terms of indentation depth evolution.